STUDI IDENTIFIKASI FASIES PENGENDAPAN DAN INVERSI SEISMIKKARBONAT LAPANGAN MASHI, CEKUNGAN JAWA TIMUR, PROVINSI JAWATIMUR - Pratama, Rizki
Moshi oil filed is one of the filed in Tuban Block East Java basin. Located near by one of the largest oil filed in Indonesia which is Cepu Block. This field is predicted had abundant oil reserves with its carbonate reservoir which is one of the Tuban Formation. To increase hydrocarbon production, geophysical and geological study applied in this field to get an better information about subsurface condition and its focus to carbonate reservoir in Moshi oil field. Data processing which is seismic inversion method and multiatribute analysis applied in purpose to find a way to seismic interpretation and show an anomaly which can be seen in normal seismic data. In this research, geophysical and geological study appied to give a description about subsurface condition in research location. Geophysical data processing consist of seismic inversion process, seismic multiatribute analysis and other process which can be helpful to get an easy way about interpretation. Geological data process consist depostional facies identification according to depositional facies model by Wilson (1975), to determine depositional environtment carbonate reservoir in this area. This serearch conclude from the seismic data processing that area with low accoustic impedance (AI) had a high porosity, whereas area with high AI had a low porosity, because the AI value corelated with the density of rocks. The same thing happened to result of the seismic multiatribute analysis, high velocity area corelated with area with tight medium. Area with good porosity, its hope can be a good oil reservoir. The result of facies identification conclude, that generally the research area depositional environtment included to depositional facies shelf lagoon open circulation with open water influence. Depositional facies difference give a different influence to reservoir quality, lithology, growth of biota and organism, difference and condition of reservoir carbonate diagenetic process. Undirectly this cause a difference of reservoir quality. Variation of depositional facies cause a different sedimentation pattern in every facies, til sedimentation pattern undirectly can influence a reservoir quality.